Multi-Level Evolution for Robotic Design - Chand, Shelvin; Howard, David (Frontiers in Robotics and AI, 2021)
Multi-level evolution (MLE) is a novel robotic design paradigm which decomposes the design problem into layered sub-tasks that involve concurrent search for appropriate materials, component geometry and overall morphology. This has a number of advantages, mainly in terms of quality and scalability. In this paper, we present a hierarchical approach to robotic design based on the MLE architecture. The design problem involves finding a robotic design which can be used to perform a specific locomotion task. At the materials layer, we put together a simple collection of materials which are represented by combinations of mechanical properties such as friction and restitution. At the components layer we combine these materials with geometric design to form robot limbs. Finally, at the robot layer we introduce these evolved limbs into robotic body-plans and learn control policies to form complete robots. Quality-diversity algorithms at each level allow for the discovery of a wide variety of reusable elements. The results strongly support the initial claims for the benefits of MLE, allowing for the discovery of designs that would otherwise be difficult to achieve with conventional design paradigms.